Altered bone marrow lymphopoiesis and interleukin-6-dependent inhibition of thymocyte differentiation contribute to thymic atrophy during Trypanosoma cruzi infection - Carbajosa, Sofía (2017)
Thymic atrophy occurs during infection being associated with apoptosis of double positive (DP) and premature exit of DP and double negative (DN) thymocytes. We observed for the first time that a significant bone marrow aplasia and a decrease in common lymphoid progenitors (CLPs) preceded thymic alterations in mice infected with Trypanosoma cruzi. In addition, depletion of the DN2 stage was previous to the DN1, indicating an alteration in the differentiation from DN1 to DN2 thymocytes. Interestingly, infected mice deficient in IL-6 expression showed higher numbers of DP and CD4+ thymocytes than wild type infected mice, while presenting similar percentages of DN1 thymocytes. Moreover, the drop in late differentiation stages of DN thymocytes was partially abrogated in comparison with wild type littermates. Thus, our results suggest that thymic atrophy involves a drop in CLPs production in bone marrow and IL-6-dependent and independent mechanisms that inhibits the differentiation of DN thymocytes.